MEDIA AS A TOOL FOR LANGUAGE DEVELOPMENT, THE LANGUAGE OF NEWS FORMULATION AS A MODEL - Mahmood, Abdul Khaleq (Humanities Journal of University of Zakho, 2025)
The research deals with an important linguistic issue, which is the problem of language development and its continuous transformations, examining the linguistic levels at which change takes place, the forms that this change takes, and explaining the role of the media as a tool in this process. The research was initiated out of the hypothesis that the media plays a fundamental role in the process of change that occurs in the body of language. The research adopted the language used in editing press news as a model to demonstrate the aspects of change that occur in the language, It consisted of two theoretical and applied parts, through the analysis of two models of three press stories separated by more than fifty years. The research concluded, after analysis and comparison, that the media has a major role in preserving the continuity of languages, through the changes it makes and on many linguistic levels, most notably the structural levels. and lexico-semantic level.